Ultra-high temperature oxidation behavior of micro-laminated ZrC/MoSi2 coating on C/C composite. (March 2018) - Xu, Jingjun; Yang, Tiantian; Yang, Yang; Qian, Yuhai; Li, Meishuan; Yin, Xiaohui
Graphical abstract: Highlights: Micro-laminated ZrC/MoSi2 coating was designed and prepared by magnetron sputtering. The morphology, structure and thickness of coating can be controlled in precise. Micro-laminated coating showed excellent anti-oxidation properties at 1800 °C in air. Oxidation mechanism of the micro-laminated coating was discussed in detail. Abstract: A protective coating with transition inner layer of SiC and micro-laminated outer layer of ZrC/MoSi2 was prepared by packaging siliconizing and magnetron sputtering on C/C composite. The total thickness of the micro-laminated outer layer was 60 μm, and the thicknesses of ZrC and MoSi2 sublayers were 4 μm and 1 μm, respectively. Ultra-high temperature oxidation test was conducted at 1800 °C for 30 min in static air. The oxidation kinetics of coated C/C composite followed parabolic law. Such attractive ultra-high temperature oxidation resistance was attributed to the formation of a dense and spallation-free oxide scale and low oxygen diffusion coefficient of ZrCx Oy .